Extracellular Vesicles of Human Periodontal Ligament Stem Cells Contain MicroRNAs Associated to Proto-Oncogenes: Implications in Cytokinesis - Chiricosta, Luigi; Silvestro, Serena; Gugliandolo, Agnese; Marconi, Guya Diletta; Pizzicannella, Jacopo; Bramanti, Placido; Trubiani, Oriana; Mazzon, Emanuela (Frontiers in Genetics, 2020)
The human Periodontal Ligament Stem Cells (hPDLSCs) exhibit self-renewal capacity and clonogenicity potential. The Extracellular Vesicles (EVs) secreted by hPDLSCs are particles containing lipids, proteins, mRNAs, and non-coding RNAs, among which microRNAs, that are important in intercellular communication. The purpose of this study was the analysis of the non-coding RNAs contained in the EVs derived from hPDLSCs using Next Generation Sequencing. Moreover, our data were enriched using bioinformatic tools. The analysis highlighted the presence of non-coding RNAs and five microRNAs: MIR24-2, MIR142, MIR335, MIR490, and MIR296. Our results show that these miRNAs target the genes classified in two terms of the Gene Ontology: “Ras protein signal transduction” and “Actin/microtubule cytoskeleton organization.” Noteworthy, the in-deep analysis of our EVs highlights that the miRNAs could be implicated in the silencing of proto-oncogenes involved in 12 different types of tumors.